Avaliação da interação de nutrientes na aplicação de zinco em sementes de arroz - de Souza, Henrique Antunes [UNESP] (2010)
The efficient fertilizer use contend micronutrient depends, also, of the interactions that occur with some nutrients. The objective was to study the interaction of zinc with the excessively nutrient ones in function of the application of different doses and sources of Zn saw seed in the culture of the rice. The experiment was carried through in conditions of vegetation house, in the FCAV/Unesp. The used experimental delineation was entirely cazualized, with three repetitions. The treatments had been five doses: 0; 1,0; 2,0; 4,0 and 8,0 g of Zn for kg of seed; e two zinc sources; sulphate of zinc (22% of Zn) and zinc oxide (50% of Zn). The experimental unit was a translucent polyethylene tray, filled with 5 washed thick sand, where 50 seeds of rice had been sown (to var. Caiapo). To the 30 days after the sowing, effected the cut of the plants, separating them in aerial part and roots. From the results of the dry substance and text of nutrients of the aerial part and root of the rice, the accumulation of the nutrients in the respective agencies of the plants was calculated. Becoming fullfilled it variance analysis and the when necessary unfoldings. It had effect of the interactions in distinguishing way between root and aerial part of rice, with regard to the doses and sources.